Workers' Task and Employer Mobility over the Business Cycle - Carlos Carrillo-Tudela; Fraser Summerfield; Ludo Visschers (Institute of Labor Economics (IZA), 2025)
We investigate cyclical changes in workers' task portfolios, highlighting their direction, magnitude, and distribution. Task changes are not only very common but provide information about the skills required across jobs. During recessions, a larger share of employer switches do not involve task changes. When changes occur, they tend to be more substantial. The cyclicality of task changes among employer-to-employer movers contrasts sharply with that of hires from unemployment. We link our findings to the “sullying” and “cleansing” effects of recessions, uncovering a novel cleansing effect associated with employer-to-employer transitions and a sullying effect tied to employer changes through unemployment.
Keywords: E32; J24; J62; E24; 330; Career Change; Occupational Mobility; Tasks; Business Cycles